KECERDASAN EMOSIONAL , IKLIM BUAYA ORGANISASI MENINGKATKAN KINERJA ORGANISASI PT ADIL MAKMUR - Rahayu Rahayu (Universitas Prof. Dr. Moestopo (Beragama), 2022)
PT. Adil Makmur strives to improve organizational performance with various strategies, especially strategies to increase human resources .To get to know about the performance of PT Adil Makmur the hypotheses that need to be answer are (1) the influence of emotional intelligence toward improves organizational performance (2) the influence of organizational culture climate toward improves organizational performance. The study design used is a combination of verificative statistic and descriptive research. , and data collection survey method with 75 employess of PT Adil Makmur, West Jawa, Indonesia as the sample by using purpose sampling technique and the analisys tool uses descriptive statistic average, and to answer the hypotheses analisys tool uses Sstruktural Eqution Method by using software Lisrel. The result show on the descriptive analysis toward the variable used is positive and some are negative. The SEM result analysis toward the hypothesis test based on imphirical data of 2 hypotheses proven are Emotional intelligence is proven to be significantly influence improves organizational performance, and organizational culture is proven to be significantly influence improves organizational performance